UNDERWATER OBSERVATIONS FROM THE SEVER-1 BATHYSTAT (PODVODNBYE NABIYUDENIYA IZ BATISTATA SERER-1) - Kuselev,O. N. (1967)
The Sever-1 bathystat was delivered to the Polar Scientific Research and Planning Institute for the Ocean Fishing Industry and Oceanography (PINRO). In August of 1960, the first voyage on the expeditionary ship Tunets to the Barents and Norwegian Seas was begun, starting our deep water investigations in the open sea. The purpose of the underwater investigations in the trawling and herring fishing areas was the performance of observations of the distribution and behavior of fish at productive depths, of the species composition and vertical distribution of plankton and, in particular, macro-plankton, and determination of the reaction of fish to light and sound. Another important task of these investigations was deciphering of the doubtful indications of sonar instruments. (Author) Trans. of mono. Development of Underwater Mine Research, n.p., n.d. p21-27.